Elaboração e avaliação da eficiência e eficácia de um programa de ensino para capacitar professores a avaliar e a intervir em situações de bullying escolar - Panosso, Mariana Gomide (Universidade Federal de São Carlos, 2019)
The effectiveness of school anti-bullying programs is directly associated to the quality of training offered to teachers, although recent researches have shown that teacher´s training courses are still insufficient on such theme. This thesis aims at implementing a programmed learning based on Programming of Conditions to Development of Behaviors (PCDB) with the aim of enabling teachers to evaluate and intervene in school bullying. This study was divided into four phases: Study 1 presents a systematic review of empirical studies on the capacity of teachers about school bullying by analyzing objectives, participants, dependent and independent variables, content and taught behaviors, training courses and their limitations. The amount of ten articles were selected from ten databases. Despite the fact that this study considered the participation of teachers, the subject of teachers’ training on bullying have been put aside by researches. Only four studies out of ten we found were dedicated to the results of training courses on the teachers’ behavior. The lack of detailed description about behaviors, contents and procedures, and the lack of based-line and follow-up have not been sufficiently taken into account. The second study (Study 2) aims at characterizing teacher´s behavioral repertoire with the purpose of assessing and intervening in school bullying. A survey research took place with 54 teachers who answered an online questionnaire composed by 19 questions. Non-parametric statistics (Spearman rho) and posteriori categorization were applied to the research results. The results showed that teachers presented a low performance in conceiving bullying or even identifying types and forms of bullying, and yet they also showed more competence on identifying the consequences of bullying over the target-student when compared to the consequences over the aggressor and spectators. Thus, it also became clear that the majority of teachers ignore protective and risk measures when students get involved in school bullying. Regarding preventive measures, most of teachers referred to “dialogue/discussions about bullying/awareness/advice” and cited different teaching methodologies, in which became clear their lack of knowledge on preventive measures against school bullying. The participants show a better understanding on dealing with the target student than the ones who engages in bullying. In conclusion, the statistics analysis demonstrated a set of 14 positive variables, of which two of them, “identifying protective variables in the school and risk variables outside the school” and “handling the aggressor´s behavior and handling the target behavior” indicated moderate correlation whilst the others maintained a weak correlation. Study 3 aimed at elaborating a programmed learning based on Programming of Conditions to Development of Behaviors (PCDB) with the aim of enabling teachers to evaluate and intervene in school bullying. This program has been designed in three stages. Stage 1: Describing a problem situation and defining the classes of behavior; Stage 2: Sequencing teaching and defining its units of learning; Stage 3: Elaborating the teaching conditions in order to define the classes of behavior. The result culminated in a program named “Identifying and intervening in school bullying” composed by 143 objective-behavior arranged into three learning units: “Characterizing and identifying acts of bullying in school context”; “Preventing school bullying”; “Handling with school bullying”. As a support material, a 65 learning-conditions manual has been drawn up to be applied in a 20-hour training course. Finally, Study 4 aimed at implementing a programmed learning based on Programming of Conditions to Development of Behaviors (PCDB) with the aim of enabling teachers to evaluate and intervene in school bullying. This study was divided into four phases: the application of a pre-test, training stage, post-test and Follow-up. During the training stage, three evaluations were implemented. In Follow-up, a evaluation and an interview on the efficiency of the teaching program have been carried out. Questionnaires were used for evaluating the dependent variables. Two lines of unique individual have been used, one AB and one of multiple based-line for behaviors. The participants´ responses were evaluated from scaling performance. The results demonstrated that the participants were most capable of conceptualizing bullying, identifying types of bullying, characterizing the target student behaviors, identifying the consequences on the target student and the spectators, identifying risk and protective variables in the school, preventing bullying and handling with the target student behavior, the aggressor and the spectators. The efficiency of the teaching program has been demonstrated by the participants’ reports about their behavior in the school and, also the resolutions of bullying cases. Participants also reported that the same behaviors have been showing in other situations of life (e.g. family and among coworkers). Developing teaching programs based on PCDB and also on the principles and procedures of Experimental Analysis of Behavior increase the probability of objective-behavior to appear in the end of training and still in the external environment.
Elaboration and evaluation of the effectiveness of a teaching program with the aim of enabling teachers to evaluate and intervene in school bullying
Keywords: Violência escolar; Capacitação de professores; Programa de ensino; Intervir em bullying; Bullying; School violence; Teacher's training; Teaching program; Bullying intervention; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::TREINAMENTO DE PESSOAL; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PROCESSOS GRUPAIS E DE COMUNICACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM